2021
DOI: 10.1039/d0ja00524j
|View full text |Cite
|
Sign up to set email alerts
|

The spectral fusion of laser-induced breakdown spectroscopy (LIBS) and mid-infrared spectroscopy (MIR) coupled with random forest (RF) for the quantitative analysis of soil pH

Abstract: Soil pH is one of the important properties of soil. The quickly and accurately determination of the pH of soil is key to realizing precision agriculture and understanding soil characteristics...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…For improving the performance of the calibration model, spectral pretreatment and variable selection strategy need to be implied in the modeling process. Common spectral pretreatment methods for LIBS mainly consist of baseline correction, noise filtering, overlapping, peak resolution, and data compression, such as multivariate scattering correction (MSC), standard normal variation (SNV), Savitzky-Golay (SG) convolution derivation, wavelet transform (WT), first-order derivation (D1st), second-order derivation (D2nd), etc. Similarly, feature selection refers to selecting the optimal feature from the original feature subset based on an evaluation criterion, which is an essential approach to improve the performance of machine learning algorithms . Variable importance measurement (VIM), variable importance projection (VIP), mutual information (MI), successive projections algorithm (SPA), genetic algorithm (GA), etc.…”
Section: Introductionmentioning
confidence: 99%
“…For improving the performance of the calibration model, spectral pretreatment and variable selection strategy need to be implied in the modeling process. Common spectral pretreatment methods for LIBS mainly consist of baseline correction, noise filtering, overlapping, peak resolution, and data compression, such as multivariate scattering correction (MSC), standard normal variation (SNV), Savitzky-Golay (SG) convolution derivation, wavelet transform (WT), first-order derivation (D1st), second-order derivation (D2nd), etc. Similarly, feature selection refers to selecting the optimal feature from the original feature subset based on an evaluation criterion, which is an essential approach to improve the performance of machine learning algorithms . Variable importance measurement (VIM), variable importance projection (VIP), mutual information (MI), successive projections algorithm (SPA), genetic algorithm (GA), etc.…”
Section: Introductionmentioning
confidence: 99%
“…27 Chen et al combined standard normal variation (SNV) spectral preprocessing and feature variable extraction methods to establish an RF calibration model based on the mid-infrared (MIR) spectra and LIBS spectra for qualitative analysis of soil pH. 18 In our previous research, we investigated the laser trapping−LIBS combined with RF to quantitatively analyze four metal elements in a single particle. 28 However, being a single particle, in the process of LIBS signal acquisition, the size of the single particle and other factors will cause instability of the spectral signal.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Multivariate calibration methods based on machine learning have been regarded as promising methods in modern spectral analysis techniques, with the advantages of higher accuracy and precision . It has been demonstrated that the accuracy of quantitative analysis of LIBS is greatly improved through spectral pretreatment and an appropriate variable extraction method from the complex LIBS spectral data matrix for eliminating the interference and then establishing the calibration model by machine learning methods, such as the random forest (RF), extreme learning machine (ELM), , artificial neural network (ANN), and support vector machine (SVM) . Among them, RF is of particular interest as a senior integrated machine learning method that has the ability to overcome over-fitting and has a large tolerance to noise and outliers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation